ANALYSIS AND FORECASTING LEVELS OF FLOOD SEVERE IN PONTIANAK CITY USING ARCGIS - Ludovicus Manditya Hari Christanto; Firda Islamaya Farhan; Ahmad Cahyono Adi (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Flood disasters often occur in areas with certain geographical conditions, such as proximity to rivers, high rainfall especially during the wetseason and soil types that contain clay so that they are not good enough to absorb water. One of the cities in Indonesia whichhas frequent floods. The planned mitigation strategy must be more targeted so that it is more effective in tackling flood disasters. Therefore, mapping with Geographic Information Systems can be used to map areas that are prone to flooding specifically by combining spatial data on each predetermined parameter. Not only that, the integration of Geographic Information Systems and forecasting with multiple linear regression methods can predict the level of flood vulnerability based on the parameters determined in the following year. Based on the analysis that has been done, the areas in Pontianak City that are prone to flood disasters are spread over several sub-districts, namely East Pontianak District, Pontianak City District and parts of North Pontianak District. Keywords: Flood vulnerability; Geographic Information System; Multiple Linear Regression  Abstrak: Bencana banjir seringkali terjadi di wilayah dengan kondisi geografis tertentu sepertijaraknya yang dekat dengan sungai, curah hujan cukup tinggi khususnya pada musim hujan hingga mayoritas jenis tanah yang memiliki kandungan lempung sehingga tidak cukup baikdalam menyerap air. Kota Pontianak merupakan satu diantara kota di Indonesia yang sering dilanda bencana banjir. Oleh karena itu, pemetaan dengan Sistem Informasi Geografis dapat digunakan untuk memetakan wilayah-wilayah yang rawan bencana banjir secara spesifik dengan menggabungkan data spasial pada setiap parameter yang sudah ditentukan. Tidak hanya itu, integrasi sistem informasi geografis dan peramalan dengan metoderegresi linier berganda dapatmemprediksi tingkat kerawanan banjir berdasarkan parameter yang ditentukan pada tahun berikutnya. Berdasarkan analisis yang telah dilakukan, daerah di Kota Pontianak yang rawan bencanabanjir tersebar di beberapa kecamatan yaitu Kecamatan Pontianak Timur, Kecamatan Pontianak Kota dan sebagianKecamatan Pontianak Utara. Kata kunci: Kerawanan Banjir; Regresi Linier Berganda; Sistem Informasi Geografis